PREPARATION OF UNIT PRICE STANDARDS (SSH) IN THE FIELD OF WATER RESOURCES AT THE PUPR OFFICE OF KERINCI REGENCY T.A 2023 (Case study of Preparation of Price Unit Standards in SiReview Laut District - Nanich Framulya (Indonesia Journal of Engineering and Education Technology (IJEET), 2023)
Theprice unit mark is an important reference in planning, supervising, and implementing a construction project. Standard unit prices also help avoid differences in price interpretation and minimize the risk of price changes that can affect success in a project. Consistentand reliable price charges for parties involved in planning activities